2020
DOI: 10.3389/fpsyg.2020.00312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Moderate-Intensity Exercise on the Mirror Neuron System: Role of Cardiovascular Fitness Level

Abstract: Objectives: The aims of this study were to use functional near-infrared spectroscopy (fNIRS) to determine whether cardiovascular fitness levels modulate the activation of the mirror neuron system (MNS) under table-setting tasks in non-exercise situation, to replicate the study that positive effect of acute moderate-intensity exercise on the MNS and investigate whether cardiovascular fitness levels modulates the effect of exercise on the activation of the MNS. Methods: Thirty-six healthy college-aged participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…Several studies have pointed out that many regions in the MNS are activated during imitation; specifically, the SMG, PMC, SMA, S1, SSAC, and ANG [11,27]. Our study confirmed this with respect to the PMC, ANG, SMG, and other MNS ROIs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies have pointed out that many regions in the MNS are activated during imitation; specifically, the SMG, PMC, SMA, S1, SSAC, and ANG [11,27]. Our study confirmed this with respect to the PMC, ANG, SMG, and other MNS ROIs.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that the PMC, ANG, SMG, and other MNS ROIs were significantly activated during imitation. Previous studies have indicated that the MNS is activated during imitation, mainly in the PMC, ANG, SMG, and SSAC [11,27]. In our participants, the average imitation time was negatively correlated with the degree of MNS activation, which indicated that the subjects achieved a better imitation performance if they had stronger internal processing.…”
Section: Discussionsupporting
confidence: 51%
“…The regions of interest (ROIs) in this study were left MNS, including left PMC (BA6), SPL (BA7), IPL (BA40), IFG (BA44/45), and other related brain regions. Based on previous studies, we designed the montage to cover left MNS according to the international 10/20 system (Figure 2A) (48,49). The montage was designed using the fOLD package and NIRSite software version 2021.4 (NIRx Medical Technologies, Minneapolis, United States) (50).…”
Section: Montage Designmentioning
confidence: 99%
“…Real-time optical morphologies of cortical hemodynamic responses can be obtained from multiple measurement locations simultaneously (40). The above technical characteristics make fNIRS suitable for the evaluation of MNS activation, and fNIRS may be the best technique to evaluate the mechanism of AE brain activation (49). The application of AOT in lower limb motor function, gait, and ADL has been gradually gaining attention, and fNIRS can be used to detect the brain activation patterns in these conditions (75-77).…”
Section: Activation Of Brain Areas During Neuromuscular Electrical St...mentioning
confidence: 99%
“…The facilitation of brain function after moderate endurance exercise further seems to extend to other regions involved in the mirror neuron network. Independent from the individual fitness level, an increased activation of inferior frontal gyrus and premotor areas during an observe-and-execute paradigm was reported after moderate endurance exercise ( 32 ). This indicates a potential pathway by which acute exercise may influence social cognitive abilities related to mirroring and motor resonance in particular.…”
Section: Central Nervous System and Social Cognitionmentioning
confidence: 99%